2016
DOI: 10.1016/j.tice.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposure to vibration is an apoptosis‐inducing stimulus in the vocal fold epithelium

Abstract: Clinical voice disorders pose significant communication-related challenges to patients. The purpose of this study was to quantify the rate of apoptosis and tumor necrosis factor-alpha (TNF-α) signaling in vocal fold epithelial cells in response to increasing time-doses and cycle-doses of vibration. 20 New Zealand white breeder rabbits were randomized to three groups of time-doses of vibration exposure (30, 60, 120 minutes) or a control group (120 minutes of vocal fold adduction and abduction). Estimated cycle-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…This study also evaluated the ultrastructure of true vocal fold epithelium. Previous reports suggest that the ultrastructure of the true vocal fold epithelium is altered with voice use and reflux disease (Franchi et al, 2007;Johnston et al, 2003;Novaleski et al, 2016). Qualitative evaluation of the overall ultrastructure of the true vocal fold epithelium was unremarkable (Figure 3).…”
Section: Histology and Ultrastructure Findingsmentioning
confidence: 86%
See 1 more Smart Citation
“…This study also evaluated the ultrastructure of true vocal fold epithelium. Previous reports suggest that the ultrastructure of the true vocal fold epithelium is altered with voice use and reflux disease (Franchi et al, 2007;Johnston et al, 2003;Novaleski et al, 2016). Qualitative evaluation of the overall ultrastructure of the true vocal fold epithelium was unremarkable (Figure 3).…”
Section: Histology and Ultrastructure Findingsmentioning
confidence: 86%
“…Animal laryngeal tissue is used because it cannot be easily or noninvasively accessed from human beings. For example, recent studies have examined the effects of phonotrauma and acid reflux using in vivo animal models (Durkes & Sivasankar, 2016;Novaleski, Kimball, Mizuta, & Rousseau, 2016). However, these studies typically involved acute exposures, sedation, or animal species with different vocal fold biology than human vocal folds.…”
mentioning
confidence: 99%
“…The vocal fold epithelium also expressed an immunohistochemical marker for apoptosis that labeled fragmented DNA. Further work using transmission electron microscopy quantified the immunohistochemical marker and morphological sign of cellular shrinkage (Novaleski, Kimball, Mizuta, & Rousseau, 2016). Results revealed that apoptosis occurred in the vocal fold epithelium after 120 min of in vivo vibration exposure compared with the same duration of vocal fold approximation only.…”
Section: Apoptosis In Vocal Foldsmentioning
confidence: 99%
“…As the most superficial layer of the vocal fold, the epithelium presents a physical barrier to the underlying lamina propria, is often considered the first line of defense against the forces of vibration, and shows structural damage following vibratory trauma [Gray, 2000;Levendoski et al, 2014;Leydon et al, 2014;Mizuta et al, 2017;Rousseau et al, 2017;Kimball et al, 2019]. As such, maintenance and repair of the epithelial barrier is critical to withstanding repeated vibratory stresses in the healthy vocal fold [Rousseau et al, 2011[Rousseau et al, , 2017Kojima et al, 2014;Novaleski et al, 2016]. Several different species have been utilized as in vivo and in vivo models of human vocal fold biology and physiology, and these include pig, dog, sheep, rabbit, and rat [Nakagawa et al, 1998;Akhtar et al, 1999;Rousseau et al, 2003;Hanson et al, 2010;Ling et al, 2010;Sivasankar et al, 2010;Alipour et al, 2011].…”
Section: Introductionmentioning
confidence: 99%